2021
DOI: 10.1111/hae.14426
|View full text |Cite
|
Sign up to set email alerts
|

Single centre, real‐world experience of perioperative rFIXFc use in adult patients with haemophilia B undergoing major and minor surgery

Abstract: Introduction: Recombinant factor IX fusion protein concentrate (rFIXFc) is increasingly used for prophylaxis in people with haemophilia B (PWHB), but experience in the perioperative setting is limited. Aims:To evaluate real-world perioperative factor usage, bleeding and complications in PWHB (≥18 years) who received rFIXFc for surgical haemostasis and to describe the treatment regimens used.Methods: Single centre, retrospective review of all PWHB who underwent a major or minor surgical procedure between June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 31 publications
(78 reference statements)
1
16
0
Order By: Relevance
“…Studies performed with the different EHL-rFIX have demonstrated that these products are effective and well tolerated for the prevention and treatment of bleeds during major orthopaedic and nonorthopaedic surgeries as well as for other minor procedure. [20][21][22][23] The efficacy and safety results were consistent with those previously reported for unmodified FIX. No FIX inhibitor, thromboembolic events or clinically significant safety issues were detected and reported in published studies.…”
Section: Ehl-rfix and Surgerysupporting
confidence: 88%
See 2 more Smart Citations
“…Studies performed with the different EHL-rFIX have demonstrated that these products are effective and well tolerated for the prevention and treatment of bleeds during major orthopaedic and nonorthopaedic surgeries as well as for other minor procedure. [20][21][22][23] The efficacy and safety results were consistent with those previously reported for unmodified FIX. No FIX inhibitor, thromboembolic events or clinically significant safety issues were detected and reported in published studies.…”
Section: Ehl-rfix and Surgerysupporting
confidence: 88%
“…The safety, efficacy and consumption of all EHL in limited number of patients undergoing surgery and invasive procedures have recently been evaluated in several pivotal trials including pegylated EHL-rFVIII, [16][17][18] Fc-Fused EHL-rFVIII, 19 Fc-fused EHL-rFIX, 20,21 albuminfused EHL-rFIX 22 and pegylated EHL-rIX. 23 As reviewed hereafter, the use of EHL concentrates impacts on the perioperative haemostatic management of surgery and invasive procedures compared SHL-FVIII/FIX.…”
Section: Invasive Procedures With Extended Half-life Fviii and Fix Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…Real‐world treatment of patients undergoing surgery with rFVIIIFc or rFIXFc in countries with similar levels of available resources as the Nordic countries has been reported in several case reports and studies 16–19,21–24,36 . Most of these report good surgical outcomes; however, only a few reports provide sufficient detail to compare dosing strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Real-world treatment of patients undergoing surgery with rFVII-IFc or rFIXFc in countries with similar levels of available resources as the Nordic countries has been reported in several case reports and studies. [16][17][18][19][21][22][23][24]36 Most of these report good surgical outcomes; however, only a few reports provide sufficient detail to compare dosing strategies. In a case report from the United Kingdom in which an adult patient with severe HA underwent a major surgery, the reported preoperative rFVIIIFc dose of 64 IU/kg was higher than the range for major surgery cases in HA reported in our results; total rFVIIIFc consumption up to Day 14 of around 279 IU/kg was lower than all but two of the major HA cases reported here.…”
Section: Discussionmentioning
confidence: 99%